DNA End Joining: G0-ing to the Core - Richard L. Frock; Cheyenne Sadeghi; Jodie Meng; Jing L. Wang (Biomolecules, 2021)
Humans have evolved a series of DNA double-strand break (DSB) repair pathways to efficiently and accurately rejoin nascently formed pairs of double-stranded DNA ends (DSEs). In G0/G1-phase cells, non-homologous end joining (NHEJ) and alternative end joining (A-EJ) operate to support covalent rejoining of DSEs. While NHEJ is predominantly utilized and collaborates extensively with the DNA damage response (DDR) to support pairing of DSEs, much less is known about A-EJ collaboration with DDR factors when NHEJ is absent. Non-cycling lymphocyte progenitor cells use NHEJ to complete V(D)J recombination of antigen receptor genes, initiated by the RAG1/2 endonuclease which holds its pair of targeted DSBs in a synapse until each specified pair of DSEs is handed off to the NHEJ DSB sensor complex, Ku. Similar to designer endonuclease DSBs, the absence of Ku allows for A-EJ to access RAG1/2 DSEs but with random pairing to complete their repair. Here, we describe recent insights into the major phases of DSB end joining, with an emphasis on synapsis and tethering mechanisms, and bring together new and old concepts of NHEJ vs. A-EJ and on RAG2-mediated repair pathway choice.